Optimalisasi Keselamatan JPL 405a Surabaya: Analisis Black Spot EAN–HAZOP dan Simulasi EWS IoT Berbasis Vissim - Nurhaliza Avrilia Wibisono; Ratih Sekartadji (International Forum of Researchers and Lecturers, 2026)
The JPL 405A level crossing in Asemrowo, Surabaya is a Category B crossing traversed by 40 train trips per day and recorded 906 traffic violations during 2021–2025, despite only two fatal crashes. This gap between high violation frequency and low accident count indicates a latent risk that may escalate into fatal incidents. This study aims to evaluate the safety and traffic performance of JPL 405A and assess the effectiveness of an Internet of Things (IoT)-based Early Warning System (EWS) as a mitigation measure. Methods include a 12-hour traffic volume survey, effective capacity calculation using PKJI 2023 with gate-closure correction, black spot identification through the Equivalent Accident Number (EAN) and Upper Confidence Limit (UCL), EAN–HAZOP risk assessment enriched with a Violation Behavior Index (IPP), and two-scenario microsimulation using VISSIM software. Results show Degree of Saturation values of 0.882 and 0.884 (LOS E) for the North and West approaches; EAN = 12 exceeds UCL = 9.705, confirming black spot status; Hazard Index reaches 4,325,360, approximately 5.8 times the regulatory threshold of 750,000; and the peak HAZOP Risk Score is 25 (Extreme Risk) for gate-running behavior. IoT EWS simulation reduced the Risk Score from 25 to 5 (Medium Risk), increased the gate-open ratio from 0.846 to 0.857, and reduced maximum queue length by 29 m (North) and 50 m (West) during peak hour. IoT EWS implementation is recommended as a medium-term priority, with flyover or underpass construction as a permanent long-term solution.